Re-inventing realities - Lehman, Cheryl R. (Emerald, 2004)
Advances in Public Interest Accounting is a research publication with two major aims. First, it aims to provide a forum for researchers concerned with critically appraising and significantly transforming conventional accounting theory, practice, teaching and research. Second, it aims to increase the social self-awareness of accounting practitioners, educators, and researchers, encouraging them to assume a greater responsibility for the profession's social role. We seek original manuscripts exploring all facets of this broad agenda. Illustrative of these aims, authors are concerned with: expanding accounting's focus beyond the behavior of individual corporate entities, encompassing the conflicts of interest within the accounting-regulatory process and effected groups; exploring alternatives to traditional economic and sociology models, beyond conventional efficiency and profitability measures of corporate performance; recognizing and examining the influences of gender and feminist theory, class and race, on accounting practice, education, and research. They are also concerned with: incorporating the significance of accounting as a communicative practice, as social dialogue, and as a social arbiter; recognizing and examining the effect of accounting practice on environmental issues and on the externalities imposed on local and global communities; examining accounting's participation in multinational expansion, consolidations, and changing economies undergoing transformations, such as Eastern and Central Europe and the Former Soviet Union, and the European Community; and, addressing the impact of new advances in information technologies.
Keywords: Business & Economics -- Accounting -- General.; Business & Economics -- Management.; Public finance accounting.; Social accounting.; Public interest.; elektronické knihy; electronic books